Falk, Rose Priola (audio interview #1 of 3) - Priola Falk, Rose (b. 6/24/1907 - d. unknown); Feichtinger, Kris, interviewer
INTERVIEW DESCRIPTION - This third interview with Rose Priola Falk was conducted as part of a special project focused on women in the ACWA in Chicago, focusing those involved with the Women's Local (275). All of these interviews conducted by Kris Feichtinger, in cooperation with the Feminist History Research Project of Los Angeles, were recorded at the ACWA union hall. The first two interviews, which focused on the union, were conducted jointly with Agnes Budilovsky. This third interview was conducted separately and focused on Falk's own background and experiences. TOPICS - family background; family history; family life; economic status; childhood; ethnic neighborhoods; and early union activism;ethnic neighborhoods; schooling; childhood; family life; household responsibilities; career expectations; early work experiences; wages; mechanization in garment industry; and attitude towards women and work; 10/28/1974